Effects of dietary nano-selenium on the growth performance, antioxidant capacity, immunity and intestinal microbiota of Tibetan naked carp (Gymnocypris przewalskii) - Yanxia Chen; Caixia He; Ying Yang; Linan Wang; Zhaonan Li; Qingchun Yan; Tianxiu Liang; Changhong Bao; Wenjie Jin; Changzhong Li (Aquaculture Reports)
This study aimed to investigate the effects of nano-selenium (nano-se) as a dietary supplement on Tibetan naked carp (Gymnocypris przewalskii) and six separate groups were conducted (0 mg/kg, NSEC; 2 mg/kg, NSE2; 4 mg/kg, NSE4; 7 mg/kg, NSE7; 9 mg/kg, NSE9; and 11 mg/kg, NSE11). The growth performance, hemato-biochemical activity, antioxidant activity, immune indices, and intestinal microbiota were subsequently measured at the end of the feeding experiment. The results showed that the hepatosomatic index, viscerosomatic index and condition factor were significantly greater in the NSE4 group (P < 0.05). The NSE4 group presented the highest specific growth rate and weight gain rate, whereas the NSE11 group presented the lowest rates. The survival rate was greater in the NSE2, NSE4, and NSE9 groups, whereas it was lowest in the NSE11 group. The contents of TP and TG and the activities of T-AOC, GSH-Px, T-SOD, CAT and GR first increased but then decreased with increasing dietary selenium content. Compared with the other groups, the NSE4 group presented comparatively lower levels of proinflammatory factors such as IL-1β, IL-6, and TNF-α, but higher amounts of lysozyme LZM and immunoglobulin IgM. The NSE4 and NSE2 groups presented considerably increased levels of anti-inflammatory factors (IL-10 and TGF-β) (P < 0.05). Dietary supplementation with an appropriate amount of nano-se can improve liver vacuolationand hepatocyte swelling in G. przewalskii, but excessive nano-se could cause liver damage. In addition, the results of intestinal microbiota detection revealed that dietary nano-se could improve the diversity of the intestinal microbiota and increase the abundance of beneficial bacteria in G. przewalskii. This research will enhance our understanding of the possible uses of nano-se and lay the groundwork for increasing the resource efficiency of G. przewalskii breeding and releasing.